Effect of calcium chloride addition on properties of acid-rennet gels. (July 2020) - Tarapata, Justyna; Smoczyński, Michał; Maciejczyk, Maciej; Zulewska, Justyna
Abstract: The effect of CaCl2 addition (2–72 mmol L −1 ) on selected properties of acid-rennet gels was investigated. Salt content in milk significantly altered the microstructure of gels as observed using scanning electron microscopy. Gels with higher content of CaCl2 (≥54 mmol L −1 ) showed more homogeneous protein network with smaller pore sizes and thus increased water holding capacity and lower cohesiveness. Fractal analysis indicated that the surface of the internal gel structure was rather irregular (fractal dimensions > 1). As revealed by atomic absorption spectrometry, demineralisation was significant and typical of coagulation caused by the presence of lactic acid that could probably cause nonsignificant correlation between calcium content in curd and some of its properties, i.e., syneresis. With the addition of 4 mmol L −1 CaCl2 to milk, a slight increase in total calcium content in the resulting curds gave a significant increase in acid-rennet gel firmness.